N-Butyl Cyanoacrylate Embolization in Management of Iatrogenic Renal Hemorrhages—Single-Center Study Evaluating Safety and Efficacy - Narkhede, Amey; Yadav, Ajit Kumar; Gupta, Arun (Journal of Clinical Interventional Radiology ISVIR, 2021)
Objectives The aim of the study was to evaluate the efficacy of endovascular N-butyl cyanoacrylate (NBCA)/glue embolization alone in the management of iatrogenic renal injuries and its effect on renal function.Methods Thirty-one patients who presented with significant iatrogenic renal injuries over a time period ranging from June 2013 to June 2018 were evaluated. The clinical features, lab parameters, and imaging findings were recorded. The embolizing agent used was exclusively NBCA. The success rate was calculated along with the effect of glue embolization on kidney in the form of postembolization ischemia and change in the serum creatinine levels in immediate pre- and postembolization period. The time between the iatrogenic injury and angioembolization as well as the time from angioembolization to discharge was also calculated. Recurrence was evaluated at 1 and 6 months follow-up.Results NBCA embolization showed 100% technical and clinical success in our study and no recurrence was noted at follow-up. Glue was also able to achieve complete embolization in patients with coagulopathy (n = 14, 45.1%). Percentage area deficit of normal renal blush in the postembolization check angiogram varied from 4 to 15.7% with a mean deficit of 7.65%. No significant difference in the serum creatinine was noted in immediate postembolization period.Conclusions We conclude that glue is an effective embolizing agent for management of iatrogenic renal injuries even in coagulopathy patients with minimal area of parenchymal loss, no significant effect on renal functions, and no recurrence on 6 months follow-up.
Keywords: NBCA; Iatrogenic renal injury; renal artery pseudoaneurysm.